Vibrational Analysis of Formic Acid - Sampath Krishnan, S.; Rajan, R.D.; Gnanasekaran, S. (Asian Journal of Chemistry, 2010)
Force constants of HCOOH and DCOOD involving seventh and second order vibrational problems have been calculated by the method of kinetic constants in conjunction with a new technique of solving the secular equation. The non-linear equations are solved by the Newton-Raphson iterative method, where the values of functions and derivatives are obtained using the new technique exploiting the symmetry in the secular equation. The other molecular constants like mean square amplitudes vibration and Coriolis coupling constants are also calculated.